2021
DOI: 10.1007/s00431-021-04335-1
|View full text |Cite
|
Sign up to set email alerts
|

Febrile seizures: perceptions and knowledge of parents of affected and unaffected children

Abstract: Febrile seizures (FS) in children are common, but little is known about parents’ perceptions and knowledge of FS. We interviewed parents of children aged 6 months to 6 years affected by FS (FS group, 65 parents) or unaffected (control group, 54 parents). In the FS group, 32% said they knew their child had an FS when the first event occurred, and 89% described fear when the child had a seizure, with a median intensity of 10/10 (Q25/Q75: 9/10). Related to follow-up, 77% in the FS group (will) observe their child… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(40 reference statements)
2
12
0
1
Order By: Relevance
“…The literature search process is reported in the Supplementary Material Figure S1 . Seven surveys (46.7%) reported an insufficient parental knowledge, suggesting the need for educational interventions ( 8 , 16 , 17 , 21 – 23 , 25 ). Huang et al conducted a survey about parental knowledge and concerns regarding FS in Taiwan and showed that the majority of involved caregivers had high concerns and inadequate knowledge on first-aid practices ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search process is reported in the Supplementary Material Figure S1 . Seven surveys (46.7%) reported an insufficient parental knowledge, suggesting the need for educational interventions ( 8 , 16 , 17 , 21 – 23 , 25 ). Huang et al conducted a survey about parental knowledge and concerns regarding FS in Taiwan and showed that the majority of involved caregivers had high concerns and inadequate knowledge on first-aid practices ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the non-clinical burden of this condition is still underestimated ( 6 , 7 ). Parental anxiety and education, as well as the direct and indirect costs associated with FS, are important factors that affect the clinical management and need for a specific focus ( 8 ). The subjective burden experienced by caregivers whose child experiences FS encompasses various dimensions, including concerns about the child's health, family dynamics, and the broader implications for public health.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although benign, with rare instances of a long term sequale, they pose a significant apprehension and anxiety to the parents. 6 Febrile seizure tend to recur in 30-50% of children following the first febrile seizure. They are seen to occur with two seasonal peaks, November to January and June to August, which correspond to peaks of viral upper respiratory infections and gastrointestinal infections respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Even though simple febrile seizures are considered benign events with an excellent prognosis [ 1 ], the phobia around them persists [ 6 , 7 ]. Pediatricians play a significant role in this phenomenon by prolonging outdated habits.…”
Section: Introductionmentioning
confidence: 99%